Effect of Prior Joint-sparing Surgery on Outcomes of First Metatarsophalangeal Joint Fusion for Treatment of Hallux Rigidus. Issue 2 (April 2022) - Rajan, Lavan; Fuller, Robert; Zhu, Jiaqi; Ellis, Scott J.
Category: Midfoot/Forefoot; Other Introduction/Purpose: Joint-sparing procedures such as cheilectomy are alternatives to first metatarsophalangeal fusion (MTPF) for treatment of hallux rigidus. These procedures have the proposed benefit of preserving joint motion and allowing for subsequent fusion if necessary. Despite the low incidence of revision after cheilectomy, some patients require subsequent MTPF due to arthritis progression or failure of symptom resolution. Prior studies have not compared outcomes between patients undergoing arthrodesis after cheilectomy and patients undergoing primary MTPF. The objective of this study was to determine if a history of a prior cheilectomy affected patient reported outcomes in patients treated with MPTF. We hypothesized that there would be no differences in outcomes between patients with and without history of prior cheilectomy. Methods: This retrospective cohort study included adult patients treated with MTPF for hallux rigidus with preoperative and minimum 1-year postoperative Patient-Reported Outcomes Measurement Information System (PROMIS) scores. Patients with no prior joint-sparing procedure (primary MTPF group) were assigned to one cohort, and patients with history of prior cheilectomy were assigned to another. Initial comparisons in preoperative PROMIS physical function (PF), pain interference (PI), pain intensity (Pint), global physical health (PH), global mental health (MH), and depression (D) scores were made using Mann-Whitney U tests. Postoperative PROMIS scores were compared using multivariable linear regression, controlling for age, BMI, gender, and preoperative scores. Wilcoxon signed rank tests were used to assess improvement in preoperative to postoperative scores in both groups. Results: A total of 127 patients (100 primary MTPF, 27 prior cheilectomy) with average follow-up of 19.6 months were included. Patient demographics including BMI, age, and gender distribution were similar between groups. Preoperative PF scores in the prior cheilectomy group were significantly worse than the primary MTPF group (median 40.5 vs 43.3, p<0.05). Table 1 illustrates the results of Wilcoxon signed rank tests demonstrating changes in scores in each PROMIS domain. There were no significant differences in postoperative PROMIS scores between the primary MTPF and prior cheilectomy groups. Conclusion: Patients undergoing MTPF for treatment of hallux rigidus both with and without a history of cheilectomy had no differences in postoperative outcomes as measured by PROMIS. Patients undergoing cheilectomy can be counseled that if the need to pursue MTPF arises due to arthritis progression or failure of symptom resolution, their postoperative function and pain after the fusion may not be affected by the cheilectomy.